Migrant protest and democratic states of exception - Arnold, Kathleen R. 1966- (New York, USA: Routledge, 2023)
"Recognizing the radical disparity between migration/border policy and constitutional law "inside these borders," Kathleen R. Arnold focuses on two main forms of migrant protest to explore the meaning of resistance in a sovereign context: self-harming protest by detainees and faith-based sanctuary of individuals scheduled for detention. This activism creates a "democratic state of exception," interrupting the legal process, altering discretionary forms of sovereign power, and enacting rights not formally granted; these efforts go beyond the assertion of liberal rights or merely restoring the rule of law (even if these are goals), challenging the warfare state while constituting a demos that is formally illegible. Migrant Protest and Democratic States of Exception will be of interest to scholars, migrant advocacy professionals (including INGO and IGO officers), graduate students, and advanced undergraduate students in a variety of fields from legal studies to forced migration and refugee studies; political science, human rights, protest history and contemporary movements"--
Introduction -- Understanding migration policy as foreign policy -- Self-harming protest -- Faith-based sanctuary: Creating spaces of democratic exception -- The sovereign exception: Is democratic sovereignty possible? -- Conclusion: States of democratic exception: Migrant agency and resistance to the warfare state.
Includes bibliographical references and index.
Keywords: Immigrants -- Political activity; Refugees -- Political activity; Protest movements; Communication -- Political aspects; Government, Resistance to; Emigration and immigration -- Government policy -- Case studies; State of siege; Detention of persons; Internment camps; Deportation